Mangrove litter production In the waters of Los Island, Tanjungpinang City, Indonesia - Depitra, Depitra; Lestari, Febrianti; Susiana, Susiana; Rochmady, Rochmady (Sangia Research Media and Publishing, 2025)
The mangrove ecosystem is one of the ecosystems that has an important role in Indonesia's coastal areas, one of which is on Los Island. Los Island is located in Senggarang Village, Tanjungpinang City, Riau Islands Province. Los Island is a small island with mangrove vegetation around the edges. This research was carried out in March-April 2024. The research location was in the waters of Los Island, Tanjungpinang City. The method used is the direct service method in the field. Determination of sampling locations was carried out using a systematic random sampling method. sampling from members of a population where the first element is selected randomly and the next element is selected systematically based on certain patterns. In sampling litter production, 10 points were taken at a distance of 200 m. Based on the results of the analysis of mangrove litter production, the average value of litter production during the 4 weeks of observation on Los Island, Tanjungpinang City was 38.24 g DW/m2. In week 1 the average value of mangrove litter production was 72.12 g DW/m². In week 2 the average value of mangrove litter production was 74.67 g DW/m². In weeks 3 and 4, the average value of mangrove litter production was 72.86 g DW/m² and 93.30 g DW/m2. The value of the mangrove decomposition rate is based on the results of the analysis of litter decomposition calculations with an average value in weeks 1 and 2 of 1.78 g/day, in week 3 of 1.70 g/day, and in week 4 a value of 1.87 g/day.